The FACTORS RELATED TO ELDER VISIT TO POSBINDU IN CIMAHI VILLAGE 2019: FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN LANSIA KE POSBINDU DI KELURAHAN CIMAHI TAHUN 2019 - Laili, Ayu (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2021)
The process of population aging certainly affects various aspects of life including social, economic, and especially health, because aging affects organs begin to lose some function, either by nature or by disease. The factors that influence elderly visit to posbindu including knowledge, attitudes, access, and family support. So that the target of elderly visit posbindu whether it has reached or not is based in the elderly’s good knowledge, positive attitudes, easy access, and support from their family. The aims of this study is to determine the factors that influence elderly to visit Posbindu in Cimahi Village. The type of this reaserch is quantitative with a cross sectional design. The sample of this study inclueded 76 elderly who lived in Cimahi Village, which was determined by proportional random sampling. The research data was collected by using a questionnare. The analysys was collected by using bivariate analysis (Chi-Square). The results of this research showed that there was a relationship between knowledge and posbindu visits (p = 0.001), there was a relationship between attitudes and posbindu visits (p = 0.001), there was no relationship between access and posbindu visits (p = 0.148), there was no relationship between family support and Posbindu visits (p = 0.643). Keywords : Elderly, Posbindu Visit